2019
DOI: 10.1111/evj.13137
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of bronchodilators in equine asthma: Looking for minimal important difference

Abstract: Summary Background Airway obstruction is the main trait of severe equine asthma that affects respiratory function and elicits detrimental effects on clinical presentation. Only few and underpowered clinical studies have investigated the impact of improvement in lung function induced by bronchodilators on the clinical signs of asthma‐affected horses. Objectives To identify the minimal important difference (MID) in lung function elicited by bronchodilator leading to a meaningful improvement in clinical signs. St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Furthermore, when disease severity was categorically graded (mild, moderate and severe) based on a linear regression curve of WCS plotted against RL, 27 a reduction in WCS of 30% ensured an improvement in at least one severity grade; namely, moderate to mild and severe to moderate (except horses which were included with a total score of ≥21). Moreover, the magnitude of change in RL underpinning the change in severity grade assessed in the dose finding studies 27 exceeded the lower limit of 0.63cmH2O/L/s (95% CI 0.33‐0.94) recently reported by Calzetta et al as the minimal change in RL which can be appreciated by a meaningful improvement in clinical signs following bronchodilator treatment of severe equine asthma 33 …”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Furthermore, when disease severity was categorically graded (mild, moderate and severe) based on a linear regression curve of WCS plotted against RL, 27 a reduction in WCS of 30% ensured an improvement in at least one severity grade; namely, moderate to mild and severe to moderate (except horses which were included with a total score of ≥21). Moreover, the magnitude of change in RL underpinning the change in severity grade assessed in the dose finding studies 27 exceeded the lower limit of 0.63cmH2O/L/s (95% CI 0.33‐0.94) recently reported by Calzetta et al as the minimal change in RL which can be appreciated by a meaningful improvement in clinical signs following bronchodilator treatment of severe equine asthma 33 …”
Section: Discussionmentioning
confidence: 75%
“…Moreover, the magnitude of change in RL underpinning the change in severity grade assessed in the dose finding studies 27 exceeded the lower limit of 0.63cm-H2O/L/s (95% CI 0.33-0.94) recently reported by Calzetta et al as the minimal change in RL which can be appreciated by a meaningful improvement in clinical signs following bronchodilator treatment of severe equine asthma. 33 Importantly, the clinical relevance of the favourable response to ciclesonide administration was further substantiated by the owner's perception of change in their horse's QoL; indeed, the percentage of ciclesonide-treated horses considered to have an improved QoL largely mirrored that of ciclesonide-treated horses with a minimum 30% improvement in WCS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, since the follow-up duration was not consistent across the RCTs, the data have been normalized as a function of person-year [26,27]. This method, supported by the Cochrane Collaboration and successfully used in recent meta-analyses [14,[19][20][21] involves the conversion of the measures into a common metric (events per person-time) prior to meta-analyzing the data, leading to improved estimates of effect, precision, and clinical interpretability of results [19,20]. Subset analyses were performed with regard to the effect of the class of monocomponents included in the FDC (LABA or LAMA).…”
Section: Discussionmentioning
confidence: 99%
“…The test for heterogeneity (I 2 ) was performed for primary endpoint to quantify the bias introduced by between-study dissimilarity, as previously reported [19], and low, moderate, and high heterogeneity was assigned for I 2 values of '25%, '50%, and '75%, respectively [20].…”
Section: Quality Score Risk Of Bias and Evidence Profilementioning
confidence: 99%